An investigation of the anti-hypertensive effect of mad honey and Rhododendron luteum sweet extract induced by N- ω -Nitro L-Arginine Methyl Ester (L-NAME) in rats (Indian Journal of Traditional Knowledge (IJTK), 2023)
The aim of this study was to investigate the anti-hypertensive effect of mad honey and Rhododendron luteum sweet extracts containing grayanotoxin (GTX)-III in a rat model of hypertension induced by N-ω-nitro L-arginine methyl ester (L-NAME). Thirty Sprague Dawley rats were divided into five groups - control (0.9% NaCl, 1 mL for 30 days, oral gavage [o.g.]), hypertensive (40 mg L-NAME /kg, bw for 30 days, intraperitoneal [i.p.]), standard (40 mg L-NAME /kg, bw for 30 days, i.p. + 20 mg Captopril/kg, bw for the last 15 days, o.g.), treatment I (40 mg L-NAME /kg, bw for 30 days, i.p. + mad honey, 12.5 mg GTX-III /kg, bw for the last 15 days, o.g.), and  treatment II ( 40 mg L-NAME /kg, bw for 30 days, i.p.+ R. luteum blossom extract, 155.8 mg GTX-III /kg, bw for the last 15 days, o.g.). In addition to evaluating blood pressure using the tail-cuff method, some biochemical parameters were also measured in serum samples. Moreover, nitric oxide (NO) and glutathione (GSH) concentrations were also analyzed in heart, liver and kidney tissues to measure tissue damage caused by hypertension. The chromatographic analyses revealed GTX-III levels in mad honey and R. luteum of 24.94±0.10 mg/kg and 155.80±0.10 mg/kg, respectively. Both extracts used for animal application had a significant anti-hypertensive effect compared to the control and captopril groups. The systolic and diastolic values of the mad honey and blossom extract groups were 157.97-164.16 and 119.92-120.47, respectively.